TAFSIR LINGUISTIK: (Studi atas Tafsir Ma'anil Qur'an Karya al-Farra') - Abdul Mustaqim (QOF, 2019)
The article tries to elaborate the linguistic interpretation of the Qur'an in the Ma'anil Qur'an written by al-Farra'. The book is considered as the first codified book of qur'anic interpretation. By using historical approach and critical-analitical method, the writer concludes that the book Ma'anil Qur'an is one of quranic interpretation colored by linguistic perspective, because al-Farra', as a writer, was well known as linguist from Kufa, aspecially in arabic grammar (Nahwu) after al-Kisai. Al-Farra' did not only interprete quranic verses to disclose the hidden meanings, but also made the interpretation of the Qur'an (tafsir) to justify and support the theory of Kufah's Nahwu.